2019
DOI: 10.1080/1461670x.2019.1639538
|View full text |Cite
|
Sign up to set email alerts
|

A User Perspective on Time Spent: Temporal Experiences of Everyday News Use

Abstract: This paper explores what spending time means from a user perspective. Drawing from three qualitative audience studies that center around the notion of experience, it reveals three complexities regarding time spent in relation to news use. Overall, we find that time spent does not necessarily measure interest in, attention to or engagement with news. First, time spent does not reflect the quality of attention being paid. Second, there is no linear relationship between time spent and interest or engagement. More… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…Clicks, shares and time spent are commonly used to measure audience engagement, which makes sense from a production perspective. Yet these metrics are limited tools to understand the user experience itself (Groot Kormelink and Costera Meijer, 2018;Groot Kormelink and Costera Meijer, 2020). Valuable journalism pertains to what, when and how people experience journalism as valuable.…”
Section: What Counts As Valuable Local Journalism From a User Perspec...mentioning
confidence: 99%
“…Clicks, shares and time spent are commonly used to measure audience engagement, which makes sense from a production perspective. Yet these metrics are limited tools to understand the user experience itself (Groot Kormelink and Costera Meijer, 2018;Groot Kormelink and Costera Meijer, 2020). Valuable journalism pertains to what, when and how people experience journalism as valuable.…”
Section: What Counts As Valuable Local Journalism From a User Perspec...mentioning
confidence: 99%
“…The average (median) time spent with a news article accessed directly was 52 seconds, compared to 54 seconds if accessed through social media and 49 seconds if arrived at through search. However, this may be because time spent with news can be challenging to measure from a technical point of view, and may not accurately reflect engagement due to individual-level differences in cognition and digital literacy (Groot Kormelink and Costera Meijer, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, others have pushed back on the emphasis of time as a benchmark for engagement. Kormelink and Meijer (2020), for example, explored the temporal aspects of news engagement and found that time is not the best measure for news interest, attention, or engagement. They found that time does not accurately represent the level or quality of the engagement and argue that spending a lot of time on a particular site can be both a sign of a lot of engagement and little engagement.…”
Section: Literature Reviewmentioning
confidence: 99%